Pengembangan Modul Berbasis Problem Based Learning (PBL) Untuk Memfasilitasi Kemampuan Berpikir Matematis Tingkat Tinggi Siswa - Siti Mutmainah; Evi Hermawati; Frendi Maulana (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
This study aims to (1) develop a module based on Problem Based Learning (PBL) to facilitate High Level Mathematical Thinking Ability (KBMTT) of students; (2) knowing the quality of PBL-based modules based on validator ratings; and (3) knowing the effectiveness of the module. This research includes development research, including the preliminary stage, the development stage, and the product testing phase. The instruments used included the PBL-based module assessment sheet and the KBMTT test. The research subjects are the parties involved during the product testing process, namely PBL-based module validators and students who will use the module. The data analysis in this study includes module development data analysis, module quality, and module usage effectiveness. The products produced from this study are PBL-based mathematical modules to facilitate high-level mathematical thinking skills equipped with learning devices.